Analysis of the type of cesarean scar pregnancy impacted on the effectiveness and safety of high intensity focused ultrasound combined with ultrasound-guided suction curettage treatment. (31st December 2022) - Peng, Yan; Dai, Yu; Yu, Guiyuan; Jin, Ping
Abstract: Objective: To investigate the clinical efficacy and safety of high intensity focused ultrasound (HIFU) combined with ultrasound-guided suction curettage in patients with type I/II/III cesarean scar pregnancy (CSP). Methods: A total of 153 patients with CSP were enrolled and classified according to the type of CSP. All of them were treated by HIFU combined with ultrasound-guided suction curettage. When active uterine bleeding was observed after curettage, a Foley balloon was used for hemostasis by compression. Baseline characteristics, technical parameters of HIFU, intraoperative blood loss in suction curettage, the time for serum β-HCG to return to normal levels, reproductive outcomes, and adverse effects were recorded and analyzed. Results: 152 patients completed one session of HIFU combined with suction curettage except one patient transferred to surgery. Total energy used for ablation and the time for serum β-HCG return to normal level in type II and III were significantly higher than type I ( p < .05). The treatment time and sonication time of HIFU in type III were significantly longer than type I ( p < .05). Vaginal bleeding after curettage and the rate of using Foley catheter balloon in type III was larger than type I and II. Conclusions: HIFU combined with ultrasound-guided suction curettage is a safe and effective treatment option for patients with type I/II/III CSP and desire for fertility. Patients with type III CSP were more dependent on Foley catheter balloon compression therapy than the other two types after HIFU combined with curettage.